2015
DOI: 10.1002/ccd.26154
|View full text |Cite
|
Sign up to set email alerts
|

Late complete atrioventricular block after closure of an atrial septal defect with a gore septal occluder (GSO™)

Abstract: Temporary intermittent complete heart block (CHB) occurred the day after interventional closure of an ASD with a 30 mm Gore Septal Occluder (GSO™) in a 2 years and 11‐month‐old female. CHB disappeared without further treatment and stable sinus rhythm recovered within 3 days. Only short episodes of 2nd degree AV‐block (Wenckebach periodicity) at rare intervals were documented in Holter‐monitors the following 2 months. Eleven months after device implantation the patient suffered from long lasting episodes of CHB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 16 publications
1
21
0
Order By: Relevance
“…It was speculated that the compression of Koch's triangle by the RA disk caused complete heart block. Dittrich et al also demonstrated a case of irreversible heart block 11 months after ASD closure using a Gore Septal Occluder that was adherent to the triangle . Our case demonstrated actual hematoma in the area 24 hr after deployment.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…It was speculated that the compression of Koch's triangle by the RA disk caused complete heart block. Dittrich et al also demonstrated a case of irreversible heart block 11 months after ASD closure using a Gore Septal Occluder that was adherent to the triangle . Our case demonstrated actual hematoma in the area 24 hr after deployment.…”
Section: Discussionsupporting
confidence: 61%
“…Temporary AV block during catheter intervention does not always preclude the device closure of the ASD; however, flow acceleration between the RA disk and the coronary sinus ostium as well as continuous contact of the RA disk on the commissure of the non‐coronary sinus and right coronary sinus of Valsalva, where the AV node is located, in the presence of intermittent AV block as seen in our case (Figure A,B) is suggestive of significant interference of the AV conduction system. In such cases, the mechanical compression should be removed by retrieving or downsizing of the disk, as the AV node dysfunction can be irreversible …”
Section: Discussionmentioning
confidence: 99%
“…Transcatheter device closure of secundum‐type atrial septal defects (ASD II) has become widely accepted as an alternative to surgical repair in patients with suitable anatomical conditions . However, cardiac erosion following implantation of closure devices remains problematic , as does the risk of device‐related complete atrioventricular block , device embolization , and mechanical device failure . Patch‐like Gore devices (W.L.…”
Section: Introductionmentioning
confidence: 99%
“…Some thought has been given as to whether the ASO device design makes it susceptible to causing AV block but the Gore Septal Occluder (GSO™)has reported as well [10]. Some studies have proposed an elevated ratio of ASO/atrial septal length and/or deficient aortic or posterior rim may be predictive of higher incidence of AV block [7,11]. Also, the decision to treat medically or remove the device is not well defined [6,10,12,13].…”
Section: Discussionmentioning
confidence: 99%